A biopsychosocial framework for understanding sexual and gender minority health: A call for action. (October 2021) - Christian, Lisa M.; Cole, Steve W.; McDade, Thomas; Pachankis, John E.; Morgan, Ethan; Strahm, Anna M.; Kamp Dush, Claire M.
Highlights: Sexual and gender minorities (SGM) are a growing proportion of the population. Marked health disparities are observed among SGM individuals. Biobehavioral pathways underlying SGM health disparities warrant attention. A Biopsychosocial Minority Stress Framework for SGM health is proposed. Existing research in this area and opportunities for knowledge acquisition are reviewed. Abstract: The number of US adults identifying as lesbian, gay, bisexual, transgender, or a different sexual identity has doubled since 2008, and about 40 % of the sexual and gender minority population identify as people of color. Minority stress theory posits that sexual and gender minorities are at particular risk for stress via stigma and discrimination at the structural, interpersonal, and individual levels. This stress, in turn, elevates the risk of adverse health outcomes across several domains. However, there remains a conspicuously limited amount of research on the psychoneuroimmunology of stress among sexual and gender minorities. We developed the Biopsychosocial Minority Stress Framework which posits that sexual minority status leads to unique experiences of minority stress which results in adverse health behavioral factors, elevated psychological distress and sleep disturbance, and immune dysregulation. Moderators in the model include both individual differences and intersectional identities. There is a crucial need to understand the biological-psychological axis of stress among the increasingly visible sexual and gender minority population to increase their health, longevity, and quality of life.